How Biblical languages work a student's guide to learning Hebrew and Greek - Silzer, Peter James; Finley, Thomas John (Grand Rapids, MI Kregel, 2004)
Includes bibliographical references.
Keywords: Hebrew language -- grammar; Greek language, biblical -- grammar; Bible. O.T. -- langage style